P03.12 Immunophenotyping of liver and lung metastases in colorectal cancer. (1st October 2020) - Schlüter, F; Dötzer, K; Prüfer, M; Bazhin, A; Werner, J; Mayer, B
Abstract : Background: Immunotherapy is an attractive strategy for second-and further-line treatment of metastatic colorectal cancer (mCRC). However, currently immune checkpoint-inhibitors are limited to the small subgroup of dMMR-MSI-H patients. Therefore additional patient stratification markers for immunotherapy independent from the MSI-status are urgently required. Materials and Methods: In this study the immune infiltrate of 53 liver and 15 lung mCRC were immunhistochemically analysed and correlated with clinicopathological parametes related to the primary tumor and the metastatic lesion and the PD-L1 status. The CD3, CD8 and PD-1 infiltrate were quantitatively counted positive cells/mm² in three different topographic regions, namely invasion margin (IM), stromal (S) and intratumoral (IT). PD-L1 expression was semiquantitatively evaluated with the cut off > 1%. The statistical analyses were performed by the Fisher`s exact-Test (two-tailed). Results: In liver metastases (LM) a high immune infiltrate of CD3 IM, CD3 S, CD8 S and PD-1 S, significantly correlated with an advanced stage (pN1/2; cM1) of the primary tumor. Independent of the type of adjuvant chemotherapy, a significantly higher fraction of CD3+ and CD8+ cells was found at the invasion margin of LM. In contrast, neoadjuvant chemotherapy induced a reduction of PD-L1 expression. Interestingly, a high CD8 IT infiltrate and a high PD-L1 expression correlated with KRAS wildtype. In addition, a high CD8 IT infiltrate and a high PD-L1 expression were found in confined LM, defined as less than two segments and unilobular distribution. A high PD-L1 expression was accompanied by a strong infiltrate of CD3, CD8 and PD-1 positive cells. In contrast, the small cohort of lung metastases showed a significant correlation for a high CD8 S infiltrate and a PD-1 IM infiltrate with right-sided metastases. Additionally, a high PD-1 IM infiltrate could be seen after neoadjuvant chemotherapy in lung metastases. Conclusions: Chemotherapeutic treatment strategy might have an impact on subsequent immunotherapy. Combination of anti-EGFR inhibitors with immunotherapy and CD3/PD-L1 Bispecific antibodies are promising options to treat liver and lung metastasis of CRC. Disclosure Information: F. Schlüter: None. K. Dötzer: None. M. Prüfer: None. A. Bazhin: None. J. Werner: None. B. Mayer: None.